Decolonizing Zakat Discourse: Rethinking the Transformation from Consumptive to Productive Zakat through Ibn ‘Āshūr’s Maqāṣid al-Sharī‘ah in the Indonesian and Malaysian Contexts - Intan Nurrachmi; Yudiyanto Tri Kurniawan; Mudrikatul Arafah; Muhammad Hanif; Taufiqurrachman; Azri Bhari (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2025)
This article critically analyzes the transformation of zakat (Islamic almsgiving) in Indonesia and Malaysia through the ethical framework of Ibn ‘Āshūr’s Maqāṣid al-Sharīʿah (Higher Objectives of Islamic Law), focusing on the key values of public good (maṣlaḥah), social justice (ʿadl), economic freedom (ḥurriyyah), and solidarity (taʿāwun). The discourse on shifting zakat distribution from consumptive to productive models has become central in contemporary Islamic social finance, particularly in debates surrounding sustainable poverty alleviation and the empowerment of zakat beneficiaries (mustaḥik). While consumptive zakat is often criticized for fostering dependency, productive zakat offers the promise of long-term socio-economic inclusion. Employing a qualitative-comparative method, this study draws on both classical and contemporary literature as well as field data from official reports of zakat institutions in Indonesia and Malaysia. The findings reveal varied degrees of alignment with the four ethical foundations. The public good (maṣlaḥah) is partially realized through measurable improvements in beneficiary income and skill development, though these outcomes often remain localized and lack integration into broader economic planning. Regarding social justice (ʿadl), the selective nature of program access and weak accountability raise concerns about fairness. Economic freedom (ḥurriyyah) remains hindered by limited capital access, inadequate institutional support, and bureaucratic rigidity, impeding beneficiaries' long-term financial independence. Solidarity (taʿāwun) is the least developed principle, as current zakat programs tend to rely on top-down implementation models that limit community participation and mutual cooperation. Theoretically, this study contributes to a decolonial rethinking of Islamic social finance by challenging charity-centric paradigms inherited from colonial frameworks. It proposes a maqāṣid-oriented vision of zakat as an emancipatory instrument of social transformation. The article advocates for participatory governance, integration with micro, small, and medium enterprise (MSME) policies, and ethical institutional reform to ensure zakat functions as a sustainable driver of socio-economic justice in Muslim-majority societies.